NUMERICAL ANALYSIS OF LIGHTWEIGHT CONCRETE WALL PANELS HAVING A VARIATION OF DIMENSIONS AND OPENINGS THAT WERE SUBJECTED TO STATIC LATERAL LOADS - Nurjannah, Siti Aisyah; Saloma; Hanafiah; Darin Putri, Nadia; Satria Albimanzura, Fadel (Journal of Applied Engineering Science, 2022)
Wall panels are non-structural parts of buildings that are considered dead loads. The mass of wall panels must be reduced to minimize earthquake risk and enhance structural resistance to lighter dead loads. This study used wall panel models that consisted of lightweight foamed concrete materials containing expanded polystyrene. The wall panels used in this study also had a variety of dimensions and reinforcements. The effect of openings on wall panel model performance was also investigated. This study aimed to analyze the performance of lightweight concrete wall panel models under static lateral loads applied until the ultimate condition. It was found that the load-deformation relation performs varying values of stiffness, strength, and ductility depended on the wall panel dimensions, reinforcements, and openings. Wall panel model with a height of 1000 mm that had length of 1500 mm and thickness of 60 mm with wire mesh and without openings achieved the highest ultimate stiffness and strength. The highest ductility was achieved by a wall panel model with openings, without wire mesh, with height, length, and thickness of 1500 mm, 1500 mm, and 40 mm, respectively. Diagrams of the deformations in this paper reflect the compressed and tensioned areas. The lefthand parts of all wall panel models without wire mesh were tensioned and had concentrations of deformation in those areas. The existence of openings also caused increased deformation due to less stiffness in the wall panel models.